Analysis of T1‐T2 stage oropharyngeal squamous cell carcinoma treated with transoral robotic surgery. Issue 1 (10th January 2023) - Li, Hui; Zhang, Xing; Chen, Wenkuan; Zhang, Quan; Li, Qiuli; Chen, Shuwei; Yang, Zhongyuan; Su, Xuan; Yan, Shida; Yang, Ankui; Song, Ming
Abstract: Objective: Transoral robotic surgery (TORS) has become an effective treatment for early‐stage oropharyngeal squamous cell carcinomas (OPSCCs). We aimed to analyze the clinical safety and efficacy of TORS for human papilloma virus (HPV)‐positive and HPV‐negative OPSCC in China. Methods: Patients with OPSCC of pT1‐T2 stage who underwent TORS from March 2017 to December 2021 were analyzed. Results: A total of 83 patients (HPV‐positive, n  = 25; HPV‐negative, n  = 58) were included. The median age of the patients was 57.0 years and 71 were men. The majority of primary tumor sites were palatine tonsils (52, 62.7%) and base of tongues (20, 24.1%). Three patients have a positive margin. A total of 12 (14.5%) patients received tracheotomies, the average duration of tracheostomy tube use was 9.4 days, and nasogastric tube was 14.5 days. No patient had a long‐term tracheotomy. The 3‐year overall survival (OS), disease‐free survival (DFS), and recurrence‐free survival (RFS) for all 83 patients were 89.5%, 80.1%, and 83.3%, respectively. The OS at 3 years between the HPV‐positive group and HPV‐negative group were 100% versus 84.3% ( P  = .07), while the DFS and RFS between two groups also showed no significant difference. Among multivariate cox regression analysis of all potential risk factors, smoking was the significant risk factors for disease recurrence ( P  < .05). Conclusion: Transoral robotic surgery achieved encouraging oncologic outcomes and safety in T1‐T2 stage OPSCC treatment, regardless of HPV status. Level of Evidence: 4 Abstract : Transoral robotic surgery achieved favorable safety and efficacy in the oncological outcomes of T1‐T2 stage oropharyngeal squamous cell carcinoma, regardless of human papilloma virus status. Therefore, the technique is safe and feasible, and worthy of clinical promotion.